Redesain User Interface pada Website Pudam Banyuwangi Menggunakan Metode User Centered Design - Rahma, Rara Dwi; Haq, Endi Sailul; Panduardi, Farizqi (Jurnal Informatika dan Komputer, 2024)
PUDAM Banyuwangi is a regional public company that provides clean water services to the community with branches in several areas. The PUDAM Banyuwangi website was built with the aim of making company information and services more accessible. It is known, during the creation of the website the company did a refresh which was carried out almost every five years to improve the functionality of the website. however, user experience testing has never been carried out measurably on the website user interface. initial testing was carried out using the User Experience Questionnaire (UEQ) as a user experience measurement tolls by getting results from 51 respondents showing the value of user experience on the website on 6 components, namely attractiveness (-0.12), clarity (0.15), efficiency (0.11), accuracy (-0.04), stimulation (-0.07), novelty (-0.29) so that it falls into the "Bad" criteria. To improve this, research was conducted using the User Centered Design (UCD) approach to analyze user needs and provide design update recommendations based on test results. The results showed that the design update increased the user experience evaluation value with an attractiveness value of (1.67), clarity (1.73), efficiency (1.71), accuracy (1.65), stimulation (1.55), novelty (1.51) so that it fell into the "Good" criteria. This can prove that this research provides recommendations for appropriate design updates to improve the functionality of the PUDAM Banyuwangi website in its development.